Preschool children handwriting evaluation on paper-based and tablet-based settings - Kamarul Aizan, Nor Lini; Mansor, Evi Indriasari; Mahmod, Ramlan (Research and Publication Unit, University of Asia Pacific, 2014)
Learning to write could be a difficult task for preschool children as they need to acquire better perceptual-motor ability during the development of their writing skills. This paper describes selected results based on the study of Arabic word writing practices with a group of 5 and 6 years old children (nonnative Arabic speakers). Children were invited to participate in a guided-writing practice activity both in paper-based and tabletbased settings. For paper based setting, children used pencil and paper sheet. In tablet setting, children were asked to use finger and stylus. Children’s performances were recorded and observed for data analysis purposes. The findings are used to suggest guidelines for improving the use of tablet for writing practice by young children.